DETOKSIFIKASI SIANIDA PADA TAILING TAMBANG EMAS DENGAN NATRIUM METABISULFIT (Na2S2O5) DAN HIDROGEN PEROKSIDA (H2O2) - Pitoi, Mariska Margaret; Wuntu, Audy D.; Koleangan, Harry S. J. (Sam Ratulangi University, 2008)
Experiments have been made to test the performance of Na2S2O5 and Cu’s method, H2O2’s method, and H2O2 and Cu’s method in cyanide detoxification in gold mining tailing with the varying theoretic concentration of the reagent was 100 %, 200 %, 300 %, 500 %, 750 %, and 1000 %. Tailing that used was taken from one of the people mining which used cyanide. It was treated with the three methods and six theoretic concentrations for four hours on magnetic stirrer. The result showed that Na2S2O5 and Cu’s method gave significant difference for CN free and CN WAD detoxification better than H2O2’s method and H2O2 and Cu’s method, whereas H2O2 and Cu’s method gave significant difference for CN free detoxification better than H2O2’s method but not for CN WAD detoxification. Theoretic concentration 750 % gave the best detoxification result but it was not have significant difference with 500 %, 300 %, and 200 % for CN free and 1000 %, 500 %, 300 %, and 200 % for CN WAD, so theoretic concentration 200 % was the economic considerations choice.